Improvement of telbivudine on renal function and massive proteinuria: A case report. (29th October 2017) - Liu, J.; Yao, N.; Zhao, Y.
Summary: The quality of life and extended survival of patients with chronic hepatitis B (CHB), especially those with decompensated liver cirrhosis, has been improved markedly with nucleos(t)ide analogs treatment. In such conditions, the influence of hepatitis B virus (HBV) infection and antiviral agents on renal function becomes a consideration with long‐term use and ageing. Membranous glomerulonephritis has been confirmed as the most common histological renal lesion. In this study, we reported a CHB patient with decompensated cirrhosis showing a significant improvement in massive proteinuria along with elevation of estimated glomerular filtration rate (eGFR) after 1 year treatment with telbivudine. However, a well‐designed study should be performed to confirm the causal association, and the molecular mechanism needs further investigation.